LATIHAN MULTIBALL DAPAT MENINGKATKAN KETEPATAN PUKULAN FOREHAND DAN BACKHAND TENIS MEJA - Nurdin, Nurdin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This research is motivated by the low accuracy of the forehand and backhand skills of tennis table players. This study aims to determine the effect of multiball training on the accuracy of forehand and backhand strokes in table tennis extracurricular students at SMPN 1 Brang Ene Taliwang, West Sumbawa Regency. This research is an experimental research. The population of this study were 16 table tennis extracurricular students. Retrieval of data using a test with the instrument the accuracy of the forehand drive and backhand drive accuracy. The data analysis technique used the t-test, through the prerequisite test for normality and homogeneity. The results of hypothesis testing using the -t test forehand strokes get of 4.710 and t table of 2.365 and backhand strokes get of 3.550 and t table of 2.365 so that it shows a significant difference in the ability of forehand and backhand strokes after being treated with multiball training. From these results it can be concluded that there is a significant effect of multiball training on the accuracy of forehand and backhand strokes in table tennis players